Valorization of Plastic Waste through Incorporation into Construction Materials - Kuok Ho Daniel Tang (Tecno Scientifica Publishing, 2022)
The growing plastic pollution has prompted the quest to reduce plastic waste sustainably and control the mismanaged plastic stream. The valorization of plastic waste through reusing and recycling has received much attention as a sustainable solution to the global plastic problem, and the construction sector provides an important avenue for such an endeavor. This review aims to present the latest advances in the valorization of plastic waste as construction and building materials through the review of 60 relevant scholarly papers and a content analysis of the papers. In the construction sector, plastic waste can be valorized as additives or raw materials for brick production. As additives, plastic waste is added at different proportions (1%–70%) with other materials, including non-plastic waste, followed by curing to acquire the desired properties. Plastic waste is used as a raw material to contain strength-imparting materials. The former has been reported to have good strengths (5.15-55.91 MPa), chemical, and thermal resistance, whereas the latter may impart lower strengths (0.67-15.25 MPa). Plastic waste is also used as additives for road pavement, primarily as substitutes for concrete-making materials, and was observed to produce desirable strengths (0.95–35 MPa) at appropriate proportions (0.5–25%), indicating the importance of optimizing the plastic contents in the concrete. Plastic waste has been recycled as plastic lumber, plastic-based door panels and gates, as well as insulation materials. Plastic-based construction materials are generally lightweight, resistant to chemicals and heat, and have good sound insulation, but they may pose a fire safety concern.